Stochastic Stability of Short-Run Market Equilibrium: A Comment - Kulkarni, Ramesh M.; Ladde, Gangaram S. (Quarterly Journal of Economics, 1979)
The stability analysis of a short-run market system under ran-dom disturbances was initiated by Turnovsky [1968]. Later on, Re-vankar [1971] observed that the selection of a Liapunov function is